Effect of combined oral contraceptive (Duofem) on platelet indices in female wistar rats - TORYILA, JOSEPH EMBERGA; K., Amadi; S.A, Odeh; U.G, Egesie; A.B, Adelaiye; A., Mohammed; L.N, Achie; D., Atsukwei (International Journal of Biological Research, 2014)
This research is aimed at determining the effect of low dose combined oral contraceptive (Duofem) on platelet count and mean platelet volume. Methods: 80 female wistar rats weighing 180 to 250g were used for the study. They were divided into four groups of 20 rats each (each group containing 10 treated and 10 control rats). The treated rat received 0.66mg/kg body weight of combined oral contraceptive intragastrically, for 36, 48, 60 and 72 days in five-day cycles (four-day treatment with one-day break). Rats in control groups remain a standard chow and water. Platelet count and mean platelet volume were determined using Symex Kx21-N Haematology auto analyzer. Results: There were no significant difference in platelet count and MPV in all the treated groups compare to the control (P<0.05). Conclusion: Low dose ethinylestradiol in combined oral contraceptive (Duofem) produces no changes in platelet count and mean platelet volume. Keywords: Combine oral contraceptive, platelet count, mean platelet volume (MPV).